Aging and bone health in Singaporean Chinese pre-menopausal and postmenopausal women - Goh, Victor; Hart, W. (Elsevier Ireland Ltd, 2016)
Objective: The study evaluated relationships between menopausal statuses, hormone replacement therapy (HRT), body mass index (BMI), percent body fat (PBF), and exercise with osteoporosis and bone mineral density (BMD) in Singaporean women. Study design: This is a cross-sectional study. Main outcome measures: The spine BMD, and femoral neck BMD as well as the prevalence of osteoporosis are the main outcome measures studied. Results: Age, BMI, PBF and exercise intensity were independently associated with spine and femoral neck BMD. Women with higher BMI and lower PBF had higher BMD and lower prevalence of osteoporosis. Postmenopausal women without HRT had lower BMD and higher prevalence of osteoporosis while those on HRT had similar BMD and prevalence of osteoporosis as premenopausal women. Conclusion: This study shows that BMI and PBF are powerful predictors of BMD. Osteoporosis is site-specific in the Singapore population, being higher in the femoral neck than in the lumbar spine. The bone status after menopause may not be worse than that dictated by age alone and both ERT and E/PRT could sustain the BMD to levels corresponding to those of women a decade younger. A strategy to improve bone health should include dieting and physical exercise program that focuses on selectively reducing fat mass and increasing lean mass.